Joel on software : and on diverse and occasionally related matters that will prove of interest to software developers, designers, and managers, and to those who, whether by good fortune or ill luck, work with them in some capacity - Spolsky, Joel (Apress, 2004)
"Someone once said that the task of a writer is to "make the familiar new and the new familiar." For years, Joel Spolsky has done exactly this at www.joelonsoftware.com. He educated us, he entertained us, and, yes, sometimes he infuriated us, but he has always made us think about what it is we are doing when we sit down in front of that blank computer screen, which is how Joel on Software became one of most popular development websites in the world. New, for the first time, you can own a collection of the most important essays from his site in one book, with exclusive commentary and new insights from Joel."--Jacket